Cultural competence in a context of ethnic tension - Eliezer Be'eri; Maurit Beeri; Tal Cohen (BMC, 2019)
Abstract This commentary describes how the first program for enhancing cultural competence in an Israeli healthcare facility was implemented at the ALYN Hospital Pediatric and Adolescent Rehabilitation Center in Jerusalem, and the lessons that can be learned from the ALYN experience for other healthcare facilities attempting to enhance their cultural competence, particularly in environments of heightened inter-cultural tension. A structured program was developed to educate hospital staff and optimize the hospital's administrative functioning towards the goal of enhanced cultural competence. The program was initiated with an international conference on site to promote awareness of the concept, and included, among other steps, the appointment of a senior administration "Coordinator of Cultural Competence", improvements in translation services, regular educational seminars, the opening of a Muslim prayer room in the hospital, and accommodations for Sabbath and Ramadan observance. Enhancing cultural competence was found to be an ongoing work-in-progress, with unanticipated cultural challenges constantly emerging, and demanding ad-hoc solutions. Some elements of the program encountered resistance from members of staff, and occasionally from members of the hospital's dominant patient cultures. Overall, enhanced cultural competence at ALYN brought benefit to both patients and the institution, ranging from a more pleasant patient experience to improved patient adherence to treatment plans, better patient-caregiver communication and a more positive and cohesive professional team and work environment.